Changes in the Cyclical Sensitivity of Wages in the United States, 1891- 1987 - Allen, Steven G. (American Economic Review, 1992)
The conventional wisdom that nominal wages became less sensitive to the business cycle and more autocorrelated after World War II is reexamined here by considering whether these properties are artifacts of the methods used to construct prewar wage series. A replication based on these methods is more cyclically sensitive and exhibits less autocorrelation than the postwar data. Aggregation using variable instead of fixed employment weights also greatly exaggerates the cyclicality of prewar wages. These biases imply that wages are just as sensitive to the cycle today as 100 years ago, perhaps even more so.